PECULIARITIES OF AMOXICILLIN AND CLAVULANIC ACID APPLICATION AMONG CHILDREN, SUFFERING FROM CHRONIC OBSTRUCTION LUNG DISEASES - O.I. Simonova; L.K. Katosova; A.V. Lazareva ("Paediatrician" Publishers LLC, 2007)
The authors review the application peculiarities of augmentin combined antibiotic (amoxicillin + clavulanic acid), analyze its efficacy during the exacerbation of the chronic obstruction bronchopulmonary process among children. They provide indications, contraindications and intake peculiarities of the given medication among children.Key words: amoxicillin, clavulanic acid, chronic obstruction lung diseases, exacerbation, children.